Influência da estimativa do gradiente horizontal troposférico no posicionamento GNSS de alta acurácia - De Oliveira Junior, Paulo Sérgio [UNESP] (2015)
The Earth's atmosphere is one of the major sources of errors in the positioning by GNSS (Global Navigation Satellite Systems). The atmosphere is divided in terms of geodetic positioning in two layers, which interact in different ways with the GNSS signals, the troposphere and the ionosphere. To mitigate the errors caused by these interactions a specific treatment is required for each layer. The troposphere is the layer from the Earth's surface up to about 50 km altitude. It is a non-dispersive medium, that is, their influence does not depend on the frequency of the signals, and one of its main effects is the tropospheric delay. In the context of GNSS data processing, it is estimated the ZTD (Zenith Tropospheric Delay), which can be subdivided into two main components: the hydrostatic and the wet one. The wet component depends on the temperature and water vapor density, along the path described by the signal. As the hydrostatic component comprises dry gases, it depends mainly on the temperature and pressure. In order to model the ZTD vertical variation usually it is employed the functions known as mapping functions, and concerning the azimuthal asymmetry it is possible to estimate the horizontal tropospheric gradients. However, there is still no consensus in the scientific community about the advantages of the horizontal gradients estimation, since the insertion of this parameter in the treatment of GNSS data has not yet been clearly evidenced, either for positioning purposes or for estimating the delay to obtain the PW (precipitable Water - precipitable water). This research aims to investigate the influence of the estimate tropospheric horizontal gradient in the high accuracy GNSS positioning on relative mode involving long baselines...